PENERAPAN SISTEM INFORMASI AKUTANSI PENJUALAN PADA PT DEHO CANNING COMPANY BITUNG - Parrangan, Gabby Angelina; Pangemanan, Sifrid S. (ACCOUNTABILITY, 2017)
The purpose of this study was to investigate the application of accounting information systems sales at PT. Deho Canning Company Bitung. Data analysis method used is descriptive analysis method. In which the author describes what is at issue, in this case the description of sales bagimana accounting information system implemented by the company. The results of this study indicate that sales accounting system applied to the PT. Deho Canning Company Bitung still manualKeywords: Accounting Information Systems, Sales